1999
DOI: 10.1108/13639519910299607
|View full text |Cite
|
Sign up to set email alerts
|

Can mental training help to improve shooting accuracy?

Abstract: The study investigated the effects of two mental training strategies separately and combined on subjects’ shooting performance following an endurance march. Further, the study examined the suitability of a ten‐session training programme for the police force. On Trial 1, following a three hour march, 44 subjects shot 25 rounds. Subjects were then randomly assigned to four groups (biofeedback, relaxation, combined biofeedback and relaxation and control). After two weeks of mental training, subjects performed bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Additional training methods may also increase officer accuracy. It has been suggested that officers who performed mental training regimens, along with firearms training, were significantly more accurate in their shooting than those who only performed single training or no training (Couture et al, 1999). It is also recommended that the next innovative stage of training would be teaching officers ‘pattern recognition’ on how to read evolving threats and intervene or control them before they become deadly for the officer.…”
Section: Discussionmentioning
confidence: 99%
“…Additional training methods may also increase officer accuracy. It has been suggested that officers who performed mental training regimens, along with firearms training, were significantly more accurate in their shooting than those who only performed single training or no training (Couture et al, 1999). It is also recommended that the next innovative stage of training would be teaching officers ‘pattern recognition’ on how to read evolving threats and intervene or control them before they become deadly for the officer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study was conducted as part of training and not in real-life shooting situations, the results indicated that the addition of night sights to firearms increased police officers'shooting accuracy in four different lighting conditions (Copay & Charles, 2001). 6 Couture et al (1999) examined the impact of two mental training strategies separately and combined on police officer shooting accuracy. Again, in a training situation, officers receiving the combined mental training regimen were significantly more accurate in their shooting than officers getting the single training and no training (Couture et al, 1999).…”
Section: Factors Influencing Hit Ratesmentioning
confidence: 99%
“…6 Couture et al (1999) examined the impact of two mental training strategies separately and combined on police officer shooting accuracy. Again, in a training situation, officers receiving the combined mental training regimen were significantly more accurate in their shooting than officers getting the single training and no training (Couture et al, 1999).…”
Section: Factors Influencing Hit Ratesmentioning
confidence: 99%
“…This is in accordance with the previous research report, namely by Copay [12], saying that the marksmanship learned in the training place was significantly influential on shooting performance. With the research subject, the police members concluded that mental training showed a significant increase in the accuracy of shootings [13].Likewise, research conducted byMaleki, Sanei, and Borhani [14] reports that military training has a significant positive effect on personalities, such as self-confidence, perfectionism, good ability, teamwork, and responsibility. Whereas the results of Kennedy's research,Kennedy and Sibley [15] say that military training serves to build a military base including noble behavior and self-confidence.…”
Section: Introductionmentioning
confidence: 91%